(untitled) (Journal of Oriental Studies, 2018)
This article deals with the two-stage funeral rites of Japan. The funerary rite of certain people reflects the whole composition of religious ideas. A detailed study of the two-stage funeral ritual reveals new approaches to the study of Japanese culture and allows a deeper understanding of the concept of a person and his posthumous fate, the concept of spiritual essences, i.e. those aspects that form the basics of any culture, as well as many customs and rituals